Development and performance evaluation of low cost soil moisture sensor for saline irrigation water - SHARMA, NAVNEET; V.M, ABDUL HAKKIM; SINGH, ATUL KUMAR (Journal of Soil and Water Conservation, 2021)
Deteriorating quality of irrigation water due to salinity has become a major problem for irrigated agriculture in India. Practicing irrigation with saline water may affect the performance of soil moisture sensors used for irrigation scheduling. This paper describes the performance of sensors used for scheduling irrigation at varying salinity levels. In the present study two types of soil moisture sensors were evaluated, out of which one was developed as low cost soil moisture sensor based on electrical conductivity and other one is based on capacitance. Developed sensor was simple, precise, sensitive, light weight and cost effective. The evaluation results revealed that the lowest value of electrical conductivity for the conductivity type sensor is 2.02 dS m-1 in distilled water and highest value of 2.4 in saline water of EC 9.9 dS m-1. At lower EC values, the data point followed a linear relationship and as the EC values increased, the relationship became nonlinear. In case of the capacitance type sensor, for different salinity levels of water (EC values) the data point followed a linear trend. The lowest value of electrical conductivity for capacitance type sensor was 0.7 dS m-1 in the distilled water and 1.36 dS m-1 in saline water of EC 9.9 dS m-1, which indicates that there is no effect of the electrical conductivity on the sensor performance in this case. Measurements using different concentration saline solutions indicated that the performance of both electrical conductivity and capacitance type soil moisture sensors are accurate and may not require specific calibration of sensors. However, limited calibration requirements are important, when large networks of soil moisture sensors are being developed.